THE INFLUENCE OF THE TIMING OF PLANTING CARROTS ON PRODUCTIVITY IN THE CONDITIONS OF KARAKALPAKSTAN - Erezhepova G.T. (International Engineering Journal For Research & Development, 2020)
The article presents the results of research on testing three terms of sowing table carrots in the Republic of Karakalpakstan. Among the tested sowing dates, the highest yield is 33,3 t/ha, formed when sowing seeds – July 10.